A GIS-BASED AUTOMATED PROCEDURE FOR LANDSLIDE SUSCEPTIBILITY MAPPING BY THE CONDITIONAL ANALYSIS METHOD: THE BAGANZA VALLEY CASE STUDY (ITALIAN NORTHERN APENNINES) - Clerici A.; Perego S.; Tellini C.; Vescovi P. (My University, 2006)
Among the many GIS based multivariate statistical methods for landslide susceptibility zonation, the so called “Conditional Analysis method” holds a special place for its conceptual simplicity. In fact, in this method landslide susceptibility is simply expressed as landslide density in correspondence with different combinations of instability-factor classes. To overcome the operational complexity connected to the long, tedious and error prone sequence of commands required by the procedure, a shell script mainly based on the GRASS GIS was created. The script, starting from a landslide inventory map and a number of factor maps, automatically carries out the whole procedure resulting in the construction of a map with five landslide susceptibility classes. A validation procedure allows to assess the reliability of the resulting model, while the simple mean deviation of the density values in the factor class combinations, helps to evaluate the goodness of landslide density distribution. The procedure was applied to a relatively small basin (167 km2) in the Italian Northern Apennines considering three landslide types, namely rotational slides, flows and complex landslides, for a total of 1,137 landslides, and five factors, namely lithology, slope angle and aspect, elevation and slope/bedding relations. The analysis of the resulting 31 different models obtained combining the five factors, confirms the role of lithology, slope angle and slope/bedding relations in influencing slope stability.
Keywords: LANDSLIDE SUSCEPTIBILITY MAP; GEOGRAPHIC INFORMATION SYSTEMS (GIS); GRASS; SHELL SCRIPT; NORTHERN ITALIAN APENNINES